COMPATIBILIZING EFFECT OF A POLY(ESTER-IMIDE) ON THE PROPERTIES OF THE BLENDS OF POLY(ETHER-IMIDE) AND A THERMOTROPIC LIQUID-CRYSTALLINE POLYMER .1. COMPATIBILIZER SYNTHESIS AND THERMAL AND RHEOLOGICAL PROPERTIES OF THE IN-SITU COMPOSITE SYSTEM - SEO, YS; HONG, SM; HWANG, SS; PARK, TS; KIM, KU; LEE, SM; LEE, J (BUTTERWORTH-HEINEMANN LTD, 1995)
This study investigates the compatibilizing effect of a poly(ester imide) (PEsI) on the blends of poly(ether imide) (PEI, Ultem 1000 from G.E.) and thermotropic liquid crystalline polymer (TLCP) (poly(ester amide), PEA, Vectra B950 from Hoechst Celanese). The compatibilizer, PEsI, was synthesized. Composite fibres were prepared by extrusion. Compatibility, thermal and rheological properties of the compatibilized in situ composite have been analysed. PEI and PEA blends are known from previous studies to be immiscible. Differential scanning calorimetry (d.s.c.) and dynamic mechanical thermal analysis (d.m.t.a.) results, however, show that PEsI is miscible with both PEI and PEA. This means that synthesized PEsI can be used as a compatibilizer for the PEI/PEA in situ composite system. The viscosity of the compatibilized in situ composite was increased by the compatibilizer owing to the strong interaction. Significant changes in the dispersion of the TLCP were observed when the compatibilizing agent was added. The size of the dispersed phase appears to be controlled by interfacial phenomena rather than rheological effects. Explanations for the interaction of PEsI with PEI and TLCP related to the interfacial phenomena are presented.
Keywords: INSITU COMPOSITES; MESOPHASE TRANSITIONS; MECHANICAL-PROPERTIES; RECRYSTALLIZATION; POLYETHERIMIDE; POLYPROPYLENE; COPOLYESTER; POLYESTER; ADHESION; FIBERS